2017
DOI: 10.15405/epsbs.2017.05.02.82
|View full text |Cite
|
Sign up to set email alerts
|

Fostering 21st Century Skills For Future Teachers

Abstract: Life and work in the 21st century demand specific skills from students in order to be successful. It is the school's and the teachers' responsibility to prepare all children for the educational demands of life and work, in a rapidly changing world, by equipping the students with the required skills. This study focuses on four skills: creativity, critical thinking, communication and collaboration, which are part of the 21st Century Skills. If teachers are expected to enable the students to use such ways of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…Orhan-Goksun (2016) found that the pre-service teachers' use of learner skills is above the medium level. In addition, Cretu (2017) found that through practicum teaching, the pre-service teachers developed some of their 21 st century skills such as communication, critical thinking, collaboration and creative learning skills. The findings of these studies concur with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orhan-Goksun (2016) found that the pre-service teachers' use of learner skills is above the medium level. In addition, Cretu (2017) found that through practicum teaching, the pre-service teachers developed some of their 21 st century skills such as communication, critical thinking, collaboration and creative learning skills. The findings of these studies concur with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…All of the international research and educational planners and theoreticians involved in the field of education have attempted to develop frameworks necessary for students to be successful in the information-based and technologydirected global society under the concept of "21 st century skills" (Cretu, 2017). In the literature, there is no universal agreement on what 21 st century skills are.…”
Section: St Century Learner Skillsmentioning
confidence: 99%
“…Changes arising from globalization, technological developments and labour market dynamics in the 21st century have influenced education. Countries' educational systems are seeking best teaching practices to educate children and young people in their daily and professional lives according to the requirements of the 21st century (Cretu, 2017). Many countries have carried out extensive curriculum reforms in the 21st century to better prepare children for the demands of life and work from higher education.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, they received feedback from colleagues, teachers, and conducted a self-analysis of micro-teaching. The way in which this experience was prepared and realized for students was widely reported in another paper [8].…”
Section: Designing Rigorous and Relevant Learning Experiences For Stumentioning
confidence: 96%
“…An authentic assessment is focused on upper-level of the knowledge taxonomy (high rigor) and challenges students to apply the knowledge to real-world problems (high relevance). The Rigor and Relevance Framework is compatible with Biggs' constructive alignment theory, which is an approach to curriculum design that optimizes the conditions for quality learning, based on: defining the intended outcomes (the objectives); choosing teaching/learning activities likely to lead to attaining the objectives; assessing students' learning outcomes to see how well they match what was intended [6,8].…”
Section: The Rigor and Relevance Frameworkmentioning
confidence: 99%